Legal Uncertainty in Fasum Land Disputes in Sampang Regency: Ketidakpastian Hukum dalam Sengketa Tanah Fasum di Kabupaten Sampang - Assyadillah, Muhamad; Khilmatus , Zhilda (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Land disputes over public facility (fasum) areas frequently arise due to conflicting claims, impacting legal and social stability. Specific Background: In Sampang District, a dispute emerged over fasum land in the